Religious Values and Aesthetic Expression in Contemporary Islamic Poetry: A Comparative Analysis of Five Selected Works - Budiman, Muhammad Arief; Muhid, Ahmad (Universitas Negeri Makassar, 2026)
This study analyzes religious values and aesthetics in five contemporary Islamic poems: Perjuangan Dakwah, He Backs Out Strong, Sightless, Mindful, The Mystery of Being Humans, and Give Me a Pen and Paper. The study aims to describe religious themes, language style, and Islamic values in these poems. A qualitative descriptive method was employed using content analysis and stylistic analysis. The results show that each poem emphasizes different aspects of religious values, including the struggle of da’wah, prayer and brotherhood, sincere love, spiritual awareness, and the power of knowledge and intellectual da’wah. Language aesthetics include metaphors, symbols, repetition, paradoxes, and acronyms that reinforce the religious messages. These findings support the view that contemporary Islamic poetry serves as a medium for da’wah, spiritual reflection, and internalization of moral values relevant to modern life.